2017
DOI: 10.1021/acs.inorgchem.7b01348
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cytotoxic Palladium(II) Pincer Complexes Based on Picolinylamides Functionalized with Amino Acids Bearing Ancillary S-Donor Groups

Abstract: The reactions of picolinyl and 4-chloropicolinyl chlorides with methyl esters of S-methyl-l-cysteine, l- and d-methionine, and l-histidine afforded a series of functionalized carboxamides, which readily formed pincer-type complexes upon interaction with PdCl(NCPh) in solution under mild conditions. The direct cyclopalladation of the ligands derived was also accomplished in the solid phase, in particular, mechanochemically, although it was complicated by the partial deactivation of the starting amides. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 88 publications
1
34
0
Order By: Relevance
“…Furthermore, it was found that the substituent at the sulfur atom only slightly affects the cytotoxicity of this type of metal complex (Table S2 in supporting information). As was expected from our previous study, none of the pyridine‐containing sulfoxide derivatives (complexes 7o – 10o ) appeared to be cytotoxic at a concentration as high as 100 μM. At the same time, their counterparts bearing the quinoline and diphenylthiophosphoryl donor groups exhibited moderate efficiencies, although the values of IC 50 were higher than those for the corresponding sulfide derivatives (entries 7 versus 5 and 8 versus 6).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, it was found that the substituent at the sulfur atom only slightly affects the cytotoxicity of this type of metal complex (Table S2 in supporting information). As was expected from our previous study, none of the pyridine‐containing sulfoxide derivatives (complexes 7o – 10o ) appeared to be cytotoxic at a concentration as high as 100 μM. At the same time, their counterparts bearing the quinoline and diphenylthiophosphoryl donor groups exhibited moderate efficiencies, although the values of IC 50 were higher than those for the corresponding sulfide derivatives (entries 7 versus 5 and 8 versus 6).…”
Section: Resultssupporting
confidence: 89%
“…In recent years, our research group has extended a range of pincer‐type palladocycles based on functionalized carboxamides with several series of complexes (see, for example, Scheme ) [3c,d,4c,7a,8,9]. Some of them demonstrated pronounced cytotoxic effects against human colon (HCT116), breast (MCF7) and prostate (PC3) cancer cells (compounds XII and XIII );[7a,8] others exhibited moderate to high catalytic activity in Suzuki cross‐coupling (compounds XIV – XVI ) . The performed investigations allowed us to outline preliminary tendencies in the structure–activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This high activity of catalysts derived from L8 led us to investigate it further. The catalysis with L8 and Table2, entries[10][11][12][13][14][15]. These results demonstrated the greater activity of the Pd-TFA catalysts than the Pd-Cl catalysts: at 60 °C, after 2 h and at 1.25 mol% catalyst loading, full conversion was observed with Pd-TFA catalysts whilst only 48% conversion was observed with the Pd-Cl catalyst (Table2, entry 12).…”
mentioning
confidence: 83%
“…In fact, following the success of cisplatin, a large number of other platinum‐based drugs have been synthesized and evaluated . Also, due to the similarity of Pd(II) to Pt(II) analogs in structure and coordination chemistry, promising biological properties as well as chemotherapeutic potential with different mechanism cause that Pd(II) complexes take attention in this field . Furthermore, in the field of non‐platinum compounds exhibiting antitumor properties, arene Ru(II) and Rh(III) complexes with an ancillary chloride ligand are promising, showing activity against cisplatin‐resistant tumors .…”
Section: Introductionmentioning
confidence: 99%